2015
DOI: 10.23939/chcht09.04.485
|View full text |Cite
|
Sign up to set email alerts
|

Alginate/κ-Carrageenan Microspheres and their Application for Protein Drugs Controlled Release

Abstract: Abstract. pH-Responsive microspheres were prepared and their feasibility as potential carriers for oral delivery of protein drugs was evaluated. The microspheres were prepared from the ionotropically-crosslinked mixture of sodium alginate and κ-carrageenan. The morphology and size of the microspheres were investigated. A model protein drug α-amylase was entrapped and in vitro drug release profiles were established. The preliminary investigation of the microspheres showed a consistent swelling pattern, high ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…[31] Furthermore, the combination of carrageenan and alginate as polymer microspheres had a lower bursting ability and had increased protection of internal material in acidic condition. [32] The only study found on the usage of the carrageenanalginate mixture in food is the development of encapsulated caffeine. [33] Other studies in carrageenan-alginate encapsulation were in the pharmaceuticals field.…”
Section: Introductionmentioning
confidence: 99%
“…[31] Furthermore, the combination of carrageenan and alginate as polymer microspheres had a lower bursting ability and had increased protection of internal material in acidic condition. [32] The only study found on the usage of the carrageenanalginate mixture in food is the development of encapsulated caffeine. [33] Other studies in carrageenan-alginate encapsulation were in the pharmaceuticals field.…”
Section: Introductionmentioning
confidence: 99%
“…65 To obtain the microspheres system with controlled release also carried out with a combination of polymers. Kolesnyk 66 makes microspheres with a combination of alginate-kappa carrageenan with the use of CaCl2 as the crosslinker. The difference in the comparison of alginate to κ-carrageenan provides a different release profile.…”
Section: Polymer Characteristics As Factor For Macrophage Targetingmentioning
confidence: 99%
“…The difference in the comparison of alginate to κ-carrageenan provides a different release profile. 66 Polymers characteristics as carrier for targeting macrophage as shown in Table 8. Mannosyltaed gelatin microsphere uptake by macrophages is higher than that of microspheres without mannosyltaed gelatin.…”
Section: Polymer Characteristics As Factor For Macrophage Targetingmentioning
confidence: 99%
“…By contrast, /-carrageenan can be extracted from wild seaweeds from cold water that are considered to be an alternative underexploited sustainable resource. 30 Preliminary works have reported the formation of carrageenan-based micro-and nanogels using an ionotropic gelation polyelectrolyte process in the presence of chitosan (carrageenan-chitosan nanoparticles) [31][32][33] or alginate (alginate-carrageenan microparticles 34 and alginate-carrageenanchitosan nanoparticles 33 ). Carrageenan-based microparticles (microspheres) were also synthesized using the spray-drying technique.…”
Section: Introductionmentioning
confidence: 99%